2001
DOI: 10.1016/s0002-9440(10)64078-3
|View full text |Cite
|
Sign up to set email alerts
|

Relocalization of Apoptosis-Inducing Factor in Photoreceptor Apoptosis Induced by Retinal Detachment in Vivo

Abstract: Apoptosis-inducing factor (AIF) is a novel mediator in apoptosis. AIF is a flavoprotein that is normally confined to the mitochondrial intermembrane space, yet translocates to the nucleus in several in vitro models of apoptosis. To investigate the role of AIF in the apoptotic process in vivo, we induced retinal detachment (RD) by subretinal injection of sodium hyaluronate, either in Brown Norway rats or in C3H mice. Apoptotic DNA fragmentation, as determined by terminal nick-end labeling, was most prominent 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
151
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 157 publications
(162 citation statements)
references
References 34 publications
10
151
1
Order By: Relevance
“…Previous studies indicated that HMGB1 could not be released from apoptotic cells 6 and the apoptotic photoreceptors were prominent in this RD model at day 3 after RD. 22 We also confirmed remarkable numbers of apoptotic photoreceptors in the detached retina at day 3 (Figure 3b), and found that the early faint TUNEL-positive nuclei had relatively low levels of HMGB1 and fragmented nuclei, which were brightly stained by TUNEL, had almost no apparent HMGB1 immunoreactivity (Figure 3c), suggesting that apoptotic dying cells might lose the expression of HMGB1 to maintain the proper gene transcription. It might be indispensable for the surviving photoreceptors to maintain and/or boost the nuclear HMGB1 in RD.…”
Section: Hmgb1 Is Present In Cultured Retinal Cell and Released Extrasupporting
confidence: 68%
See 2 more Smart Citations
“…Previous studies indicated that HMGB1 could not be released from apoptotic cells 6 and the apoptotic photoreceptors were prominent in this RD model at day 3 after RD. 22 We also confirmed remarkable numbers of apoptotic photoreceptors in the detached retina at day 3 (Figure 3b), and found that the early faint TUNEL-positive nuclei had relatively low levels of HMGB1 and fragmented nuclei, which were brightly stained by TUNEL, had almost no apparent HMGB1 immunoreactivity (Figure 3c), suggesting that apoptotic dying cells might lose the expression of HMGB1 to maintain the proper gene transcription. It might be indispensable for the surviving photoreceptors to maintain and/or boost the nuclear HMGB1 in RD.…”
Section: Hmgb1 Is Present In Cultured Retinal Cell and Released Extrasupporting
confidence: 68%
“…22 Briefly, the rats were anesthetized with an intramuscular injection of ketamine and xylazine, and their pupils were dilated with topical 1% tropicamide and 2.5% phenylephrine hydrochloride. The retinas were detached using a subretinal injection of 1% sodium hyaluronate (Opegan; Santen, Osaka, Japan) with an anterior chamber puncture to reduce intraocular pressure.…”
Section: Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…42,43 In addition, the distribution of AIF expression in nondiabetic retinas observed in the present study is consistent with a previous animal study. 44 Diabetic retinas showed upregulation of cytochrome c and AIF immunoreactivity. Our data for cytochrome c in diabetic retinas are in agreement with several studies reporting increased cytochrome c immunoreactivity and activity in the retina postaxotomy and following optic nerve crush 43,45 suggesting that one of the early responses in the retina after optic nerve injury is to scale up the energy production.…”
Section: Discussionmentioning
confidence: 97%
“…The sections were incubated with the secondary antibody for 1 h. Terminal deoxynucleotidyl transferase-mediated dUTP nick end-labeling (TUNEL) costaining was performed using an ApopTag Fluorescein In Situ Apoptosis Detection Kit according to the manufacturer's protocol (Chemicon, Temecula, CA, USA). 17 The slides were counterstained with 4,6-diamidino-2-phenylindole (DAPI), mounted with Shandon PermaFluor (Thermo Scientific, Waltham, MA, USA), and viewed with an Olympus fluorescence microscope (Olympus, Tokyo, Japan). Images were obtained using the same exposure time for each comparative section.…”
Section: Immunofluorescence Staining and Transmission Electron Microsmentioning
confidence: 99%